Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.7 - Inverse Functions - 2.7 Exercises - Page 229: 83


$(f~o~g)^{-1}=2\sqrt[3] {(x+3)}$

Work Step by Step

$f~o~g=f(g(x))=f(x^3)=\frac{1}{8}x^3-3~~$ (Replace $f~o~g$ by $y$): $y=\frac{1}{8}x^3-3~~$ (Interchange $x$ and $y$): $x=\frac{1}{8}y^3-3$ $x+3=\frac{1}{8}y^3$ $y^3=8(x+3)$ $y=\sqrt[3] {8(x+3)}$ $y=2\sqrt[3] {(x+3)}$ $(f~o~g)^{-1}=2\sqrt[3] {(x+3)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.